Analisis Hubungan Komposisi Unsur SiO₂ pada Material Tuf Vulkanik Lampung di Hatta Bakauheni Menggunakan Portable XRF sebagai Metode Pendukung Kemagnetan Batuan dalam Menentukan Sifat Magnetiknya - Novia Deswira; Hamdi Rifai; Ahmad Fauzi; Harman Amir (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates the relationship between SiO₂ composition and magnetic properties of Lampung Tuff from Hatta Bekauheni using an integrated approach combining rock magnetism and portable geochemical analysis. Magnetic susceptibility measurements were conducted using a Bartington MS2B sensor at low and high frequencies to determine χlf and χfd (%), while elemental composition was analyzed using Portable X-Ray Fluorescence (Portable XRF). The results indicate that all samples exhibit ferrimagnetic behavior, reflecting the presence of magnetic minerals such as magnetite or titanomagnetite with varying concentrations and grain sizes. The χfd (%) values suggest a mixture of superparamagnetic and coarser grains, indicating heterogeneous depositional and post-depositional processes. SiO₂ content varies among samples, representing local geochemical differentiation of volcanic material. However, regression analysis shows a very weak correlation between SiO₂ and magnetic parameters, as indicated by low coefficients of determination. These findings demonstrate that magnetic properties are primarily controlled by mineralogical factors rather than silica composition. The integration of magnetic susceptibility and Portable XRF provides an efficient, non-destructive framework for comprehensive volcanic material characterization.